Electronic Government and Accountability: Systematic Literature Review, Framework, and Agenda for Future Research - Antoni, Syafrul; Rahayu, Sri; Yudi, Yudi; Herawary, Netty (Journal of Applied Business, Taxation and Economics Research, 2024)
Electronic government (e-government) is an effective tool to enhance accountability in public organizations. However, the implementation of e-government to enhance accountability remains unclear and involves many complex processes due to multiple accountabilities disorder. The e-government elements that contribute to mitigating the disorders and dysfunctions of accountability relationships are still underdeveloped in the current literature. This paper aims to provide an understanding of how e-government can enhance organizational accountability by reviewing the relevant literature. This research employs a systematic literature review methodology using PRISMA reporting guidelines. The authors searched for scholarly articles in the online Elsevier (Scopus) database, written in English and accessible in full text. The study utilizes data from 18 articles to conduct the systematic literature review. The findings indicate that most previous studies on the impact of e-government on accountability were published in 2009 and 2010. Additionally, the findings show that developed countries dominate the research locations with a total of 16 articles, while only 2 articles pertain to developing countries. The predominant methodology used in studies on the impact of e-government on accountability is website content analysis, accounting for 9 articles.